(3OdGdI GdTcd Ydi cejI GdCcds - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3fMeO Gddg Ydi cd MGd jMQe GdCcd ahb GdTHY EdG EPG MUd GdVYa hdGJLhR GdQjGVI HJbdjd GdCcd MJi jVYa Yf COGA GdYHGOGJ s
(3BNQgG (B:s
(3Ccd HCUHYg GdKdGK HGdEHgGe hGdJi JdjgG hGdhSWi, Ke QCjJg jdYb CUGHYg GdKdGK bHd Cf jeSMgG, hjdYb GdhSWi Ke GdJi jdjgG Ke GdEHgGe s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B95 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs